Microexons: novel regulators of the transcriptome. Issue 1 (1st January 2018) - Curry-Hyde, Ashton; Chen, Bei Jun; Mills, James D.; Janitz, Michael
Abstract: Alternative splicing of RNA is a fundamental post-transcriptional regulatory process that leads to a vast diversity of proteins being translated from a relatively small number of genomic loci. Microexons, a set of very small protein-coding sequences of 1-17 amino acids, have only recently been recognised as an important part of pre-mRNA processing. Recent studies have revealed that microexons can play important roles in various cellular functions, protein-protein interactions and have also been associated with various neurological diseases. This review provides an update on research covering the functional impact of microexons on the biology of a cell and disease, and the mechanisms by which their splicing is regulated. Finally, the current bioinformatics methods for detecting microexons are discussed.